Exploring the Potential of Chalcogenide Lens Designs for Cost-effective LWIR Systems - Liu Chang (EPJ Web of Conferences)
The high cost of optical raw materials in the long wavelength infrared (LWIR) region necessitates the development of cost-effective solutions without compromising resolution. Chalcogenide glasses offer a faster and easier production process compared to growing single crystals of Germanium (Ge). Additionally, they can be molded into complex optical surfaces, reducing processing costs further for serial production. In this study, we explore the potential of chalcogenide lenses. Our comprehensive design study demonstrates that chalcogenide lens designs can achieve comparable or even superior optical performance with reasonable system complexity when compared to a wide-angle benchmark Ge design.